Development Of Soil Nutrients Monitoring Using Smart Grid System - Mohammed Ali Asban; Suhana Mohamed Sultan; Rahmat Talib (Progress in Engineering Application and Technology, 2022)
Agriculture is considered the basis of life for humans as it is the main source of food. Food security has become a vital global concern in recent years due to the increase in pollution, climate change, and high demand due to the increase in population. Moreover, there are some challenges in agriculture that farmers face recently such as water utilization, crops monitoring, and soil fertilization. In this paper, a grid system is developed using IoT technology to monitor the soil moisture level, pH value, and nutrient parameters remotely. The result shows that the pH value, soil moisture, and nutrients measured from the respective sensors provide reliable data to users. The average moisture level of 70% is achieved and a 6.4 pH value is obtained for the crop soil. The collected data is visualized via the smartphone application for real-time monitoring. This proposed IoT system can improve the quality of soil resources and reduce the extra use of water and fertilizers.